An Academic Analysis of Digital Transformation: A Comprehensive Review of Literature and Business Strategies - Fadhlurrahman, Muhammad Alfi (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2024)
The idea of digital transformation has an impact on many different facets of business. The goal of this study is to examine how digital transformation affects businesses, industries, and society as a whole, with a particular emphasis on business models, operational procedures, and customer experience. To examine the definitions, components, pillars, and important facets of digital transformation, this study uses a literature review methodology. The review's findings show that using digital technology to modernize corporate processes and improve productivity, responsiveness, and creativity is included in the concept of digital transformation. The components of digital transformation are also described in this study, including business models, digital platforms, employee experience, customer experience, and operational procedures within the organization. The customer experience, business models, and operational procedures of the organization are the three primary pillars of digital transformation. In addition, there are five essential components of digital transformation: value, data, customers, competition, and innovation. In a connected and quickly evolving business environment, digital transformation is becoming more and more significant, and firm executives need to have a long-term vision to take advantage of the potential.